Construction of Parseval Framelets Associated with GMRA on Local Fields of Positive Characteristic. (17th February 2021) - Ahmad, Owais; Bhat, Mohammad Younus; Sheikh, Neyaz Ahmad
Abstract: In this article, we establish theory of Parseval framelets associated to generalized multiresolution analysis (GMRA) in the setting of reducing subspace for the local field of positive characteristics (LFPC). We develop the unitary extension principle for Parseval framelets associated to GMRA on LFPC. The procedure for the construction of Parseval framelets is also established. An example is also provided at the end.